The Courtship Novel, 1740-1820 : A Feminized Genre - Green, Katherine Sobba, 1949- (Book collections on Project MUSE., 1991)
The period from her first London assembly to her wedding day was the narrow span of autonomy for a middle-class Englishwoman in the eighteenth and early nineteenth centuries. For many women, as Katherine Sobba Green shows, the new ideal of companionate marriage involved such thoroughgoing revisions in self-perception that a new literary form was needed to represent their altered roles. That the choice among suitors ideally depended on love and should not be decided on any other grounds was a principal theme among a group of heroine-centered novels published between 1740 and 1820. During these d.